Physicians’ Perspectives about Consent in Medical Practice: A Questionnaire-Based Study - Sherin Prabu Raja; Dipayan Deb Barman (Indian Journal of Forensic Medicine and Pathology, 2026)
Background: Consent is an ethical and legal requirement in medical practice. Informed consent involves obtaining the patient’s permission and ensuring the patient’s complete understanding of the nature, purpose, risks, and alternatives of a medical procedure. In India, awareness and practice with consent among medical students and professionals vary. Aim: To assess understanding, attitudes, and practices regarding medical consent among medical students and trainees. Methodology: A questionnaire-based study was conducted among 181 practitioners and Interns with 11 questions on physicians’ perspectives on consent. Results: Awareness of various types of consent in medical practice was reported by 149 participants (82.32%). Regarding a child over 12 years of age giving valid consent for a simple examination, 36.46% agreed. In cases involving intoxicated individuals, 70.17% believed consent should be obtained from police and examination done with minimal force. About telephonic consent, 60.77% rejected it in the absence of attenders. Most participants (70.17%) supported regular CME sessions on consent and medical ethics. The majority (76.80%) agreed that proper consent and documentation prevent negligence charges. Conclusion: The study showed that while most participants have a good theoretical understanding of consent in medical practice, their knowledge of specific legal provisions and exceptional circumstances remains incomplete. The majority recognise the importance of written informed consent and documentation in preventing medical negligence, but uncertainty persists regarding consent from minors, intoxicated individuals, and consent obtained telephonically. We recommended incorporating structured teaching modules on medical ethics, consent, and medico-legal and conducting periodic Continuing Medical Education sessions.